Reversible Protein Adsorption on Mixed PEO/PAA Polymer Brushes: Role of Ionic Strength and PEO Content - Bratek-Skicki, Anna; Eloy, Pierre; Morga, Maria; Dupont-Gillain, Christine (Langmuir, 2018)
Proteins at interfaces are a key for many applications in the biomedical field, in biotechnologies, in biocatalysis, in food industry, etc. The development of surface layers that allow to control and manipulate proteins is thus highly desired. In previous works, we have shown that mixed polymer brushes combining the protein-repellent properties of poly(ethylene oxide) (PEO) and the stimuli-responsive adsorption behavior of poly(acrylic acid) (PAA) could be synthesized and used to achieve switchable protein adsorption. With the present work, we bring more insight into the rational design of such smart thin films by unravelling the role of PEO on the adsorption/desorption of proteins. The PEO content of the mixed PEO/PAA brushes was regulated, on the one hand, by using PEO with different molar masses and, on the other hand, by varying the ratio of PEO and PAA in the solutions used to synthesize the brushes. The influence of ionic strength on the protein adsorption behavior was also further examined. The behavior of three proteins-human serum albumin, lysozyme, and human fibrinogen, which have very different size, shape, and isoelectric point-was investigated. X-ray photoelectron spectroscopy, quartz crystal microbalance, atomic force microscopy, and streaming potential measurements were used to characterize the mixed polymer brushes and, in particular, to estimate the fraction of each polymer within the brushes. Protein adsorption and desorption conditions were selected based on previous studies. While brushes with a lower PEO content allowed the higher protein adsorption to occur, fully reversible adsorption could only be achieved when the PEO surface density was at least 25 PEO units per nm . Taken together, the results increase the ability to finely tune protein adsorption, especially with temporal control. This opens up possibilities of applications in biosensor design, separation technologies, nanotransport, etc.